2023
DOI: 10.1101/2023.03.22.23287383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developing contents for a digital drug adherence tool with reminder cues and personalized feedback: a formative mixed-methods study among children and adolescents living with HIV in Tanzania

Abstract: Children and adolescents living with HIV (CALHIV) form a significant proportion of people living with HIV (PLHIV). Optimal adherence (>95%) to medication is needed to achieve viral suppression. However, optimal adherence remains a challenge among CALHIV. Digital adherence tools (DAT) like the Wisepill® device have proven feasible among adult PLHIV. Still, there are concerns about unwanted disclosure of HIV status due to content in short message service (SMS) that serve as reminders. We assessed the needs, c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…23 Multiple studies have shown that RTMM-based DATs are acceptable among PLHIV and are feasible in resourcelimited settings. [24][25][26][27][28] However, the major concern with RTMM-based DATs is the possibility of unwanted HIV status disclosure due to the triggered reminder SMSs and concerns of invasion of privacy. 29 Although most studies have reported good feasibility of the intervention, some have reported technical challenges such as poor network as barriers to effective implementation of RTMM-based interventions.…”
Section: Introductionmentioning
confidence: 99%
“…23 Multiple studies have shown that RTMM-based DATs are acceptable among PLHIV and are feasible in resourcelimited settings. [24][25][26][27][28] However, the major concern with RTMM-based DATs is the possibility of unwanted HIV status disclosure due to the triggered reminder SMSs and concerns of invasion of privacy. 29 Although most studies have reported good feasibility of the intervention, some have reported technical challenges such as poor network as barriers to effective implementation of RTMM-based interventions.…”
Section: Introductionmentioning
confidence: 99%